Corporate Governance and Executive Compensation in Zimbabwean State Owned Enterprises: A Case of Institutionalized Predation - Farai Ncube; Langtone Maunganidze (Scientific & Academic Publishing, 2023)
The study critically explores the strengths and limitations of the current corporate governance systems to adequately monitor and control top executive behavior in the State owned enterprises (SOEs) The study focuses on executive compensation in the form of the hefty salaries and allowances in these organisations albeit a depressed economic performance that has left both their staff and stakeholders in states of penury. The paper questions the ethical issues emanating from such practices and the ‘reluctance’ of government to dictate and intervene in time. The delayed response was not just an under-estimation of the problem but some kind of complicity. The paper argues that the corporate governance structures in state owned enterprises in Zimbabwe have unceasingly become too fragile to restrain both the development and escalation of executive over-compensation. The practice has been reduced to a kind of institutionalised corruption which has been exacerbated by seemingly state of willingful blindness. Using the co-evolutionary model of predation the study shows how the exponential rise in corruption in the macro-environment has been matched by a culture of ‘feeding from service’ particularly in state owned enterprises.